Visualization of SNARE-Mediated Hemifusion between Giant Unilamellar Vesicles Arrested by Myricetin - Heo, Paul; Park, Joon-Bum; Shin, Yeon-Kyun; Kweon, Dae-Hyuk (Frontiers in Molecular Neuroscience, 2017)
Neurotransmitters are released within a millisecond after Ca2+ arrives at an active zone. However, the vesicle fusion pathway underlying this synchronous release is yet to be understood. At the center of controversy is whether hemifusion, in which outer leaflets are merged while inner leaflets are still separated, is an on-pathway or off-pathway product of Ca2+-triggered exocytosis. Using the single vesicle fusion assay, we recently demonstrated that hemifusion is an on-pathway intermediate that immediately proceeds to full fusion upon Ca2+ triggering. It has been shown that the flavonoid myricetin arrests SNARE-mediated vesicle fusion at hemifusion, but that the hemifused vesicles spontaneously convert to full fusion when the myricetin clamp is removed by the enzyme laccase. In the present study, we visualized SNARE-mediated hemifusion between two SNARE-reconstituted giant unilamellar vesicles (GUVs) arrested by myricetin. The large size of the GUVs enabled us to directly image the hemifusion between them. When two merging GUVs were labeled with different fluorescent dyes, GUV pairs showed asymmetric fluorescence intensities depending on the position on the GUV pair consistent with what is expected for hemifusion. The flow of lipids from one vesicle to the other was revealed with fluorescence recovery after photobleaching (FRAP), indicating that the two membranes had hemifused. These results support the hypothesis that hemifusion may be the molecular status that primes Ca2+-triggered millisecond exocytosis. This study represents the first imaging of SNARE-driven hemifusion between GUVs.